200PApalutamide (APA) plus androgen deprivation therapy (ADT) for metastatic castration-sensitive prostate cancer (mCSPC): Analysis of pain and fatigue in the TITAN study. (24th November 2019) - Chung, B H; McQuarrie, K; Bjartell, A; Chowdhury, S; Pereira de Santana Gomes, A J; Özgüroğlu, M; Juárez Soto, Á; Merseburger, A S; Uemura, H; Ye, D; Given, R; Miladinovic, B; et al.
Abstract: Background: TITAN demonstrated that APA + ADT improves radiographic progression-free survival and overall survival over placebo (PBO) + ADT in patients (pts) with mCSPC, including those with low- and high-volume disease, previous docetaxel use, and prior treatment for localized disease (Chi KN N Engl J Med 2019). The likelihood of meaningful deterioration in pt-reported pain and fatigue in TITAN is explored. Methods: mCSPC pts were randomized 1:1 to receive either APA (240 mg daily; n = 525) or PBO (n = 527), in addition to continuous ADT; each treatment cycle (C) was 28 days. Pain and fatigue were assessed using the Brief Pain Inventory-Short Form (BPI-SF) and Brief Fatigue Inventory (BFI), at baseline and averaged over 7 consecutive days (D) (D -6 through D1 of each C). General estimating equations for logistic regression were used to estimate treatment-related differences in likelihood of worsening in pain or fatigue scores (worsening of ≥ 2 points in items from BPI-SF and BFI). Results: Median scores for pain (APA, 1.14; PBO, 1.00) and fatigue (APA, 1.29; PBO 1.43) on 0-10 severity scales indicated all pts were relatively asymptomatic at baseline. Pts treated with APA vs PBO consistently scored favorably in all BPI-SF pain severity– and pain interference–related questions, and had significantly lower risk of worsening pain interference with mood (p = 0.015), sleep (p = 0.044), and overall pain interference (p = 0.032; Table). Reduced risk of overall pain interference was observed by C18. In general, pt experience with fatigue was similar with APA and PBO (Table). Conclusions: In a broad population of pts with mCSPC in TITAN, no additional pt-reported fatigue was observed with the addition of APA or PBO to ADT. Pts reported consistently favorable pain scores and less interference from pain in their daily lives with APA. Clinical trial identification: NCT02489318. Editorial acknowledgement: Editorial assistance was provided by Patricia McChesney, PhD, CMPP, of Parexel (Hackensack, NJ), and was funded by Janssen Research & Development. Legal entity responsible for the study: Janssen Research & Development. Funding: Janssen Research & Development. Disclosure: B.H. Chung: Research grant / Funding (self), Travel / Accommodation / Expenses: Janssen (USA & Korea); Research grant / Funding (self): Bayer (Germany); Research grant / Funding (self): Pfizer (USA); Research grant / Funding (self): AstraZeneca (UK); Research grant / Funding (self): Roche (Switzerland); Research grant / Funding (self): Myovant Sciences GmbH (Australia); Travel / Accommodation / Expenses: Astellas (Korea); Travel / Accommodation / Expenses: Ipsen (Korea); Travel / Accommodation / Expenses: JW Pharma (Korea); Travel / Accommodation / Expenses: Takeda (Korea); Travel / Accommodation / Expenses: Handok (Korea); Travel / Accommodation / Expenses: Amgen (Korea). K. McQuarrie: Full / Part-time employment: Janssen Research & Development; Shareholder / Stockholder / Stock options: Johnson & Johnson. A. Bjartell: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses, Non-remunerated activity/ies: Janssen; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Astellas; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses, Non-remunerated activity/ies: Bayer; Advisory / Consultancy, Travel / Accommodation / Expenses, Non-remunerated activity/ies: Incyte; Honoraria (self), Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Ferring; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: IPSEN; Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Officer / Board of Directors: LIDDS Pharma; Research grant / Funding (self), Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Officer / Board of Directors, Non-remunerated activity/ies: Glactone Pharma/Development ; Shareholder / Stockholder / Stock options: WntResearch. S. Chowdhury: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Johnson & Johnson; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Astellas; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Sanofi; Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Travel / Accommodation / Expenses: Clovis. Á. Juárez Soto: Advisory / Consultancy, Speaker Bureau / Expert testimony, Non-remunerated activity/ies, Publication Steering Committee TITAN & IP Clinical Trial SPARTAN: Janssen. A.S. Merseburger: Travel / Accommodation / Expenses, Non-remunerated activity/ies, support for clinical trial conduct: Janssen Cilag; Travel / Accommodation / Expenses, Non-remunerated activity/ies, support for clinical trial conduct: Astellas Pharma; Travel / Accommodation / Expenses, Non-remunerated activity/ies, support for clinical trial conduct: Roche. H. Uemura: Speaker Bureau / Expert testimony, Research grant / Funding (self): Janssen; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Takeda; Research grant / Funding (self): Astellas; Speaker Bureau / Expert testimony, Research grant / Funding (self): Ono/BMS; Research grant / Funding (self): Taiho; Speaker Bureau / Expert testimony: Pfizer; Speaker Bureau / Expert testimony: Bayer; Speaker Bureau / Expert testimony: MSD; Speaker Bureau / Expert testimony: Novartis. R. Given: Speaker Bureau / Expert testimony: Janssen. B. Miladinovic: Full / Part-time employment: Janssen Research & Development; Shareholder / Stockholder / Stock options: Johnson & Johnson. N. Li: Full / Part-time employment: Janssen Research & Development; Shareholder / Stockholder / Stock options: Johnson & Johnson. S. Hudgens: Full / Part-time employment: Clinical Outcomes Solutions; Travel / Accommodation / Expenses: Janssen Research & Development. L. Floden: Full / Part-time employment: Clinical Outcomes Solutions; Travel / Accommodation / Expenses: Janssen Research & Development. A. Lopez-Gitlitz: Full / Part-time employment: Janssen Research & Development; Shareholder / Stockholder / Stock options: Johnson & Johnson. K.N. Chi: Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Institutional: Janssen; Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Institutional: Astellas; Research grant / Funding (institution), Travel / Accommodation / Expenses, Institutional: Essa ; Research grant / Funding (self), Research grant / Funding (institution), Travel / Accommodation / Expenses, Institutional: Sanofi; Travel / Accommodation / Expenses, Institutional: Bayer; Research grant / Funding (institution), Travel / Accommodation / Expenses, Institutional: Roche; Research grant / Funding (institution), Travel / Accommodation / Expenses, Institutional: AstraZeneca. N. Agarwal: Advisory / Consultancy: Astellas; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Argos; Advisory / Consultancy: Bristol Myers Squibb; Advisory / Consultancy: Bayer; Advisory / Consultancy: Clovis; Advisory / Consultancy: Eisai; Advisory / Consultancy: Exelixis; Advisory / Consultancy: EMD Serono; Advisory / Consultancy: Ely Lilly; Advisory / Consultancy: Foundation One; Advisory / Consultancy: Genentech; Advisory / Consultancy, Travel / Accommodation / Expenses: Janssen; Advisory / Consultancy: Merck; Advisory / Consultancy: Medivation; Advisory / Consultancy: Novartis; Advisory / Consultancy: Nektar; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Pharmacyclics. All other authors have declared no conflicts of interest.